1981
DOI: 10.1007/bf00126933
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of Crotalaria V. Supernumerary nucleoli in C. agatiflora (Leguminosae)

Abstract: Of 35 species of Crotalaria (Leguminosae) studied, all but one had usually one nucleolus in the premetaphase I cells. In C. agatiflora 300 PMCs from four out of five plants were investigated and the percentage cells with more than one nucleolus was determined as well as the nature of nucleolar attachment to bivalents and the range and the sizes of various nucleoli present in the cell. The "aberrant' cells ranged from 42 to 50%. The nucleoli (1-6) were usually attached to different bivalents. Where one nucleolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…1996). And some authors reported on a new locus of 18S rRNA gene in chromosomes of a cultiwtted clone of Allium xativum in Chma (Hizume ct al., 19951, on variabilily of the number of nucleoli in Crotalaria (Verma and Raina, 1981), and on the occurrence of additional rDNA with NOR-forming ability in the intercala U heterochromatin of Drosophila (llyin et al, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…1996). And some authors reported on a new locus of 18S rRNA gene in chromosomes of a cultiwtted clone of Allium xativum in Chma (Hizume ct al., 19951, on variabilily of the number of nucleoli in Crotalaria (Verma and Raina, 1981), and on the occurrence of additional rDNA with NOR-forming ability in the intercala U heterochromatin of Drosophila (llyin et al, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…1980; Verma & Raina, 1981;Fernández-Piqueras et a!., 1983;Cabrero et a!., 1987). However, we do not think that the additional NOR of M. trossulus constitutes a latent NOR, because this region is shown to have a different heterochromatin from the NORs of M. edulis and M gaioprovincialis (chromosomes 6 and 7 are CMA3 positive, whereas chromosome 8 from M. 1995 The Genetical Society of Great Britain, Heredity, 74,4. trossulus is CMA3 negative).…”
Section: Chromosomal Markers In Genus Myt/lus 373mentioning
confidence: 92%
“…Translocations and inversions of the chromosomes are unlikely, given the Cband and telomere probe data. Hybridization in genetically diverse populations or other stimuli could cause NORs to behave as mobile genetic elements (Ilyin et al" 1978;Verma and Raina, 1981). These genes move in and out of the chromosomes either by a transposase mechanism or via reinsertion at sites that show sequence homology with the insert.…”
Section: Resultsmentioning
confidence: 99%
“…The mobility of genes varies, with some genes, such as the 18S and 28S ribo somal genes, being conservatively confined to a few chromo somal positions within a species. Some reports, however, de scribe populations in which the chromosomal location of the ribosomal genes differs within and between populations of the same species (Nardi et al" 1977;Schmid, 1978;Verma and Raina. 1981;Shubert and Wobus.…”
mentioning
confidence: 99%